The Influence of Social Support, Career Decision-Making Self-Efficacy, and Career Optimism on Student Career Adaptability (Case Study of Private University Students in Semarang City) : The Influence of Social Support, Career Decision-Making Self-Efficacy, and Career Optimism on Student Career Adaptability (Case Study of Private University Students in Semarang City) - Cahya, Ardya Fitria; Ervina Indiworo, Rr Hawik; Putri, Noventia Karina (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The research aims to examine and analyze the influence of social support, career decision-making self-efficacy, and career optimism on student career adaptability (Case study of private university students in Semarang City). This type of research is quantitative research. The population in this study were private university students in Semarang City with a sample size of 100 students. The data collection technique is through a questionnaire in the form of a google form, then the data is processed through the IBM SPSS Statistics version 26 application with multiple linear regression analysis.This research shows that social support has no effect on students' career adaptability, career decision-making self-efficacy has a positive and significant effect on students' career adaptability and career optimism has a positive and significant effect on students' career adaptability. Based on the test results of the coefficient of determination R with an Adjusted R Square value of 0.332 or 33.2%.